APLIKASI MICROSOFT TEAMS DALAM MENINGKATKAN KETERAMPILAN MENULIS ESAI - Franscy, Franscy; Hidayati, Dini; Solo, Lenny; Zahari, Musril (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to determine the effectiveness of the Microsoft Teams application in teaching essay writing skills to students in class XI SMA Bangun Cipta Rumbia, Lampung. Based on the result of preliminary observation shows that students learning outcome was still low and there were some problems related to the impact of their writing skills that still have not achieved the expected aims. This research used the action research method, involving 30 students. Quantitative data was taken from the results of comparing the results of writing essays on initial conditions (pre-cycle), cycle 1, and cycle 2, while qualitative data was taken during observation and action. The results showed that there was an increase in learning activities and learning outcomes in writing essays for students. This increase is known from the percentage of students' activeness in participating in the learning process has increased, the results obtained in cycle 2 the percentage of "very active" and "active" was 30% and the percentage of "less active" and "very less active" decreased by 23.33%. The results of students' essay writing skills also increased, this increase can be seen from the percentage of the mastery score of essay writing in Cycle 1 of 63.33%, then experienced a significant increase in Cycle 2 with the percentage of completeness value of 73.33%. This means that the application of the Microsoft Teams application based on technological developments has a positive impact on the development of students in the learning process, especially essay writing skills.